Preventing Gender-Based Violence Among Adolescents and Young Adults: Lessons From 25 Years of Program Development and Evaluation - Crooks, Claire V.; Jaffe, Peter; Dunlop, Caely; Kerry, Amanda; Exner-Cortens, Deinera (Violence against women, 2019)
Effective prevention of intimate partner violence (IPV) among adolescents and young adults is a key strategy for reducing rates of gender-based violence (GBV). Numerous initiatives have been developed and evaluated over the past 25 years. There is emerging evidence about effective strategies for universal prevention of dating violence in high school settings and effective bystander interventions on university and college campuses. In addition, there have been some effective practices identified for specific groups of youth who are vulnerable to victimization (either based on past experiences of exposure to domestic violence or previous dating victimization). At the same time, though our evidence about school and college-based interventions has grown, there are significant gaps in our knowledge of effective prevention among marginalized groups. For example, there is a lack of evidence-based strategies for preventing IPV among Indigenous youth; lesbian, gay, bisexual, transgender, questioning+ [LGBTQ+] youth; and young women with disabilities, even though these groups are at elevated risk for experiencing violence. Our review of the current state of evidence for effective GBV prevention among adolescents and young adults suggests significant gaps. Our analysis of these gaps highlights the need to think more broadly about what constitutes evidence. We identify some strategies and a call to action for moving the field forward and provide examples from our work with vulnerable youth in a variety of settings.